Implementation of Inclusive Education at Aisyiyah Kindergarten Branch V Martapura - Soraya Soraya; Muhammad Yusuf; Uswatun Nisa (CV. Edujavare Publishing, 2025)
Early childhood education is recognized globally as the most critical period for optimizing holistic child development cognitive, social-emotional, language, and moral. This study aims to describe and analyze the implementation of inclusive education at TK Aisyiyah Ranting V Martapura, focusing on planning, implementation, and evaluation of learning for children with special needs (CWD). The research employed a descriptive qualitative approach with data collection techniques including observation, interviews, and documentation. Data analysis employed the Miles and Huberman model, which consists of four stages data reduction, data coding, data display, and conclusion drawing. The findings reveal that inclusive education planning has been carried out over the past two years but remains limited to administrative aspects, lacking adequate support in the form of Individualized Education Plans (IEPs). Implementation is conducted through collaborative and individual approaches, however, limited facilities and human resources present significant challenges. Evaluation is carried out informally through teacher observations and communication with parents, without standardized formal instruments. The analysis indicates that the success of inclusive education is strongly influenced by teacher commitment, flexibility in teaching approaches, and parental involvement. However, program sustainability requires stronger policy support, specialized training, and collaboration with external experts.